A Study on the Impact of Globalization on MSMEs in Indonesia - Andarweni Astuti; Ferani Mulianingsih; Amin Pujiati; Ambrosius Heri Krismawanto (Soegijapranata Catholic University, 2023)
The purpose of this study is to analyze the impact of globalization on MSMEs in Indonesia in the context of prior of the Covid-19 pandemic. The study applied descriptive qualitative approach and used documentation as the data collection in which the data were retrieved from journals, web, and other relevant sources. The results concluded that MSMEs in Indonesia with 10% contribution had not been able to significantly support the Indonesian economy due to various obstacles. The government has taken various ways to overcome this problem and expected that by 2024 MSMEs can support 17% of the national economy.